Overview of ReCoRES at IberLEF 2022: Reading Comprehension and Reasoning Explanation for Spanish; Overview de ReCoRES en IberLEF 2022: Comprensión de Lectura y Explicación de Razonamiento en Español - Sobrevilla Cabezudo, M.A.S.; Diestra, D.; López, R.; Gómez, E.; Oncevay, A.; Alva-Manchego, F. (Sociedad Espanola para el Procesamiento del Lenguaje Natural, 2022)
This paper presents the ReCoRES task, organized at IberLEF 2022, within the framework of the 38th edition of the International Conference of the Spanish Society for Natural Language Processing. The main goal of this shared-task is to promote the task of Reading Comprehension and Verbal Reasoning. This task is divided into two sub-tasks: (1) identifying the correct alternative in reading comprehension questions and (2) generating the reasoning used to select an alternative. In general, 3 teams participated in this event, mainly proposing transformer-based neural models in conjunction with additional strategies. The results of this event, insights and some challenges are presented, opening a range of possibilities for future work.
Keywords: Reading comprehension; Verbal reasoning; Transformer models; https://purl.org/pe-repo/ocde/ford#1.02.01